The Video encyclopedia of the 20th century, vol. 66, [nos.] 2084-2096 [videorecording]. ([S.l.] CEL Communications, 1986)
It shows particular historical events that occured in the 1900's, and focuses on the outstanding personalities associated with each event.
VHS.
Keywords: Aquino, Benigno S. -- Assassination, 1983.; Encyclopedias and dictionaries -- 20th century; Library science